Design a model of glass cleaning device - Nguyen, Van Khanh; Nguyen, Chi Ngon; Nguyen, Huynh Anh Duy (CTU Journal of Innovation and Sustainable Development, 2017)
Design and create a supportive automatic device for labors working on cleaning vertical glasses on the skyscrapers has been one of the concerned topic in the issue of occupational safety recently. This study will recover briefly the main points of designing mechanical structure with a new idea after referring the previous works in glass cleaning robot. The trapezoidal velocity profile (TVP) method is mentioned in order to control the velocity of the device; and the movement strategy for cleaning glass is considered carefully while manufacturing the model of the device. The experiment has been conducted on a dirty glass with the size of 1.45m x 0.85m, this proved a good initial result which has met the expected requirement for a low-power device.